Joint forces and moments calculation for a 3D whole body model during complex movement Application to the balance recovery movement following a support surface translation - Robert, T.; Cheze, L.; Dumas, R.; Verriest, J. P. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
The purpose of this study was to calculate the joint forces and moments for a complete human body model during 3D complex movements of balance recovery. A 40-dof body model was used. The movements were measured using an optoelectronic system and reconstructed using a semi-global optimization method. The joints forces and moments were calculated through a classical Newton-Euler recursive algorithm. The consistency of the computed loads was checked by comparing the results of different calculation strategies. The first attempts with classical hypotheses showed poor results. A sensitivity analysis was lead to determine the most critical parameters. Thus, investigations were performed to improve the estimation of the position of the centers of mass and the derivation of the kinematic parameters. The use of 3D regression equations for the estimation of the Body Segment Inertial Parameters and the use of the residual analysis to adjust the filters cut-off frequencies allowed major improvements of the quality of the solutions. The results obtained that way were found to be meaningful.